INOVASI PEMBELAJARAN STEM: SINERGI ANTARA EKOSISTEM DAN ENERGI ALTERNATIF DALAM PAMERAN KARYA SISWA KELAS X MAS INSAN QUR’ANI - Hasanah, Mauizah; Rosma, Fatemah; Aldyza, Nadia; Harahap, Vivi Yunisa (Jurnal Dedikasi Pendidikan, 2025)
This study aims to describe the effectiveness of project-based learning with the theme "Synergy of Ecosystems and Alternative Energy" in improving 21st century skills and conceptual understanding of class X students of MAS Insan Qur'ani. The problems raised are low student engagement and lack of development of 21st century skills in conventional learning. The study was conducted in February 2025 with 136 students as subjects through total sampling techniques. Data were collected using student activity observation sheets, student response questionnaires, and work exhibition assessments. The analysis was carried out descriptively quantitatively using percentage techniques. The results showed that students were active, creative, able to work together, understand concepts, and show high responsibility, with an average activity score of 85.2%. Student responses were also very positive, with the highest score in the aspect of exhibition benefits (91%). Project exhibitions such as terrariums, dioramas, and solar panels became an authentic means of displaying understanding and innovation, with terrariums getting the highest score (average 89.6). In conclusion, project-based learning is effective in improving students' engagement, conceptual understanding, and critical thinking skills, collaboration, communication, and creativity in a meaningful and contextual manner